Life in a fishbowl: Prospects for the endangered Devils Hole pupfish (Cyprinodon diabolis) in a changing climate. Issue 8 (27th August 2014) - Hausner, Mark B.; Wilson, Kevin P.; Gaines, D. Bailey; Suárez, Francisco; Scoppettone, G. Gary; Tyler, Scott W.
Abstract The Devils Hole pupfish (Cyprinodon diabolis) is a federally listed endangered species living solely within the confines of Devils Hole, a geothermal pool ecosystem in the Mojave Desert of the American Southwest. This unique species has suffered a significant, yet unexplained, population decline in the past two decades, with a record low survey of 35 individuals in early 2013. The species survives on a highly variable seasonal input of nutrients and has evolved in a thermal regime lethal to other pupfish species. The short lifespan of the species (approximately 1 year) makes annual recruitment in Devils Hole critical to the persistence of the species, and elevated temperatures on the shallow shelf that comprises the optimal spawning habitat in the ecosystem can significantly reduce egg viability and increase larval mortality. Here we combine computational fluid dynamic modeling and ecological analysis to investigate the timing of thresholds in the seasonal cycles of food supply and temperature. Numerical results indicate a warming climate most impacts the heat loss from the water column, resulting in warming temperatures and reduced buoyancy‐driven circulation. Observed climate change is shown to have already warmed the shallow shelf, and climate change by 2050 is shown to shorten the window of optimum conditions for recruitment by as much as 2 weeks. While there are many possible reasons for the precipitous decline of this species, the changing climate of the Mojave region is shown to produce thermal and nutrient conditions likely to reduce the success of annual recruitment of young C. diabolis in the future, leading to continued threats to the survival of this unique and enigmatic species.